Transformasi Manajemen Mutu Pendidikan melalui Kepemimpinan Visioner dan Inovasi Digital - Rosmiati Ramli; Kurnia Alex; Rosiana Syahbaniar; Fitriani Muh Amin; Rudihartono Rudihartono (Journal of Humanities, Social Sciences, and Education, 2026)
Educational transformation in the digital era demands educational institutions to implement adaptive, innovative, and sustainable quality management. Visionary leadership and digital innovation are two strategic factors capable of driving improvements in educational quality in the face of increasingly complex environmental changes. This article aims to analyze the transformation of educational quality management through the application of visionary leadership and digital innovation based on the results of a literature review. The study uses a library research method with a descriptive-qualitative approach. Data were obtained from various scientific sources in the form of reputable national and international journal articles, books, proceedings, and policy documents published in the 2020–2025 period. Data analysis was carried out through a systematic process of data reduction, classification, synthesis, and drawing conclusions. The results of the study indicate that visionary leadership plays a crucial role in building a culture of quality through the development of a strategic vision, data-driven decision-making, human resource empowerment, and strengthening collaboration between all stakeholders. On the other hand, digital innovation supports the effectiveness of quality management through the utilization of school information systems, digital learning platforms, educational data analytics, and artificial intelligence in decision-making. The integration of these two aspects results in a quality management system that is more responsive, efficient, transparent, and oriented towards continuous improvement. This study confirms that the success of educational quality transformation depends not only on the use of technology but also on the leadership's ability to direct organizational change in a visionary and sustainable manner. The research findings are expected to serve as a conceptual reference for school principals, education administrators, and researchers in developing educational quality management models that meet the demands of the digital era.